Limitations to the Right to Freedom of Assembly in Poland during the COVID-19 Pandemic: The Case of Women’s Strike - Osiewicz, Przemysław (HAPSc Policy Briefs Series, 2020)
The ongoing COVID-19 pandemic poses a threat not only to public health and human life, but also to civil rights and freedoms. Such a claim applies not only to authoritarian states, but also to democratic political structures. Significant restrictions on civil liberties were introduced under the pretext of ensuring security in at least several member states of the European Union. One of them is Poland. The main purpose of this paper is to examine causes, developments, and consequences of the limitations to the right to freedom of assembly in Poland influencing the activities of the social protest movement Women’s Strike (Strajk Kobiet) during the ongoing pandemic. The text concludes recommendations both for the Women’s Strike social movement and for the government. Their implementation should reduce the current tensions in Poland and enable the opening of constructive social dialogue.